ANALISIS DAN EFISIENSI PEMASARAN MINYAK NILAM DI DESA KUBU KECAMATAN ARONGAN LAMBALEK KABUPATEN ACEH BARAT - Agustiar Agustiar; Ibnu Sa’adan (Jurnal Bisnis Tani, 2016)
received to consume to patchouli oil marketing, as well the research method used survey method by purposive sampling and quantitatif analyze. The result showed the availability of two pattern of patchouli oil marketing channels. Farmers, traders, wholesalers and exporters, as well as farmers, wholesalers and exporters. Share on channel I by farmers received amount by 84,28%, or amount by Rp 561,250 kg-1 of the selling price by Rp 661.250 kg-1. And channel II by 86,77% or amount by Rp 573.750 kg-1 of the selling price by Rp 661.250 kg-1. To share of marketing margin amount to 13,23% of the overall marketing margin amount by Rp 87.500 kg-1.